New Insights into the Spontaneous Human Alzheimer's Disease-Like Model Octodon degus: Unraveling Amyloid-β Peptide Aggregation and Age-Related Amyloid Pathology - Cisternas, Pedro; Zolezzi, Juan M.; Lindsay, Carolina; Rivera, Daniela S.; Martinez, Alexis; Bozinovic, Francisco; Inestrosa, Nibaldo C. (My University, 2018)
Alzheimer's disease (AD) is the most common cause of dementia worldwide. Despite advances in our understanding of the molecular milieu driving AD pathophysiology, no effective therapy is currently available. Moreover, various clinical trials have continued to fail, suggesting that our approach to AD must be revised. Accordingly, the development and validation of new models are highly desirable. Over the last decade, we have been working with Octodon degus (degu), a Chilean rodent, which spontaneously develops AD-like neuropathology, including increased amyloid-beta (A beta) aggregates, tau hyperphosphorylation, and postsynaptic dysfunction. However, for proper validation of degu as an AD model, the aggregation properties of its A beta peptide must be analyzed. Thus, in this study, we examined the capacity of the degu A beta peptide to aggregate in vitro. Then, we analyzed the age-dependent variation in soluble A beta levels in the hippocampus and cortex of third- to fifth-generation captive-born degu. We also assessed the appearance and spatial distribution of amyloid plaques in O. degus and compared them with the plaques in two AD transgenic mouse models. In agreement with our previous studies, degu A beta was able to aggregate, forming fibrillar species in vitro. Furthermore, amyloid plaques appeared in the anterior brain structures of O. degus at approximately 32 months of age and in the whole brain at 56 months, along with concomitant increases in A beta levels and the A beta(42)/A beta(40) ratio, indicating that O. degus spontaneously develops AD-like pathology earlier than other spontaneous models. Based on these results, we can confirm that O. degus constitutes a valuable model to improve AD research.
Keywords: alzheimer's disease; a beta peptide; natural model; octodon degus; senile plaques